Feasibility of using signal strength indicator data to estimate soil moisture based on GNSS interference signal analysis. Issue 1 (2nd January 2018) - Yan, SongHua; Zhang, Nan; Chen, NengCheng; Gong, JianYa
ABSTRACT: The use of multipath signals to estimate soil moisture is an important application of Global Navigation Satellite System (GNSS) reflectometry. In most studies the data used to estimate the soil moisture are raw signal to noise ratio (SNR) data. However, the SNR data are only regarded as auxiliary data used to determine the quality of signal in most of the widely distributed Continuous Operational Reference System (CORS) receivers. So SNR data are generally ignored and unavailable. Fortunately, the GNSS receivers output the standard data format as Rinex, where the Signal Strength Indicator (SSI) is recorded as alternative data to SNR. This study aims to investigate the feasibility of soil moisture estimation based on SSI data. An experiment was conducted to estimate SSI phase and record the in situ soil moisture data for comparison. Then the relationship between the phase and soil moisture is determined by 44 days SSI data processing. Finally, the relationship is used to further estimate soil moisture with 36 days data. Experimental results show the correlation coefficient between the SSI phase and in situ soil moisture is approximately 0.7, and that the root mean square estimation error of soil moisture is lower than 9.9%. Results demonstrate the feasibility of using SSI data to estimate soil moisture.